Muscle-Enriched MicroRNAs Isolated from Whole Blood Are Regulated by Exercise and Are Potential Biomarkers of Cardiorespiratory Fitness - Denham, Joshua; Prestes, Priscilla R. (Frontiers in Genetics, 2016)
MicroRNAs (miRNA) are small non-coding RNA molecules that regulate gene expression post-transcriptionally. Evidence indicating miRNAs influence exercise-induced health and performance adaptations is mounting. Circulating microRNAs are responsible for intercellular communication and could serve as biomarkers for disease and exercise-related traits. Such biomarkers would contribute to exercise screening, monitoring and the development of personalised exercise prescription. Accordingly, we investigated the impact of long-term strenuous aerobic exercise training and a single bout of maximal aerobic exercise on five muscle-enriched miRNAs implicated in exercise adaptations (miR-1, miR-133a, miR-181a, miR-486 and miR-494). We also determined linear correlations between miRNAs, resting heart rate and maximal oxygen uptake (V ̇O2max). We used TaqMan assay quantitative PCR to analyse the abundance of miR-1, miR-133a, miR-181a, miR-486 and miR-494 in resting whole blood of 67 endurance athletes and 61 healthy controls. Relative to controls, endurance athletes exhibited increased miR-1, miR-486 and miR-494 content (1.26–1.58-fold change, all p<0.05). miR-1, miR-133a and miR-486 were decreased immediately after maximal aerobic exercise (0.64–0.76-fold change, all p<0.01) performed by 19 healthy, young men (20.7±2.4 y). Finally, we observed positive correlations between miRNA abundance and V ̇O2max (miR-1 and miR-486) and an inverse correlation between miR-486 and resting heart rate. Therefore, muscle-enriched miRNAs isolated from whole blood are regulated by acute and long-term aerobic exercise training and could serve as biomarkers of cardiorespiratory fitness.